Analyzing Board Characteristics, Ownership Structure and Company Characteristic to CSR Disclosure - Kirana, Asyifa Dea; Prasetyo, Andrian Budi (Universitas Negeri Semarang, 2021)
This study aims to analyze the effect of board characteristics, ownership structure and company characteristics on CSR disclosure. The population of this study are non-financial companies that listed on the Indonesia Stock Exchange (IDX) which issues sustainability reports separately from the annual report for the year 2017-2018. Based on the purposive sampling method as a method of data collection, a total of 20 non-financial companies have published sustainability reports separately from the annual reports for 2017 and 2018 respectively. Multiple regression analysis used to test the research hypotheses. The results of this study indicate that the proportion of women on the board, board of director ownership concentration, profitability and leverage negatively affect the CSR, while the rest of variables does not affect the CSR disclosure. Keywords: CSR disclosure; board characteristics; ownership structure; company characteristics; sustainability report